Los músicos en Cali: profesión, prácticas y público en el siglo XX - Llano, Isabel (Sociedad y Economía, 2004)
The situation of the professional musicians in Cali at the end of the Twentieth Century is relatively precarious and unstable, due mainly to the absence of a solid art market and to the presence of weak sponsorship. This occurs in spite of the clear advances of the professionalization of music along the whole century. This is validated when one examines the relationships between musical institutions and public audiences, the dominant musical practices and its restrictions, the composition of the musical field and the symbolic wars led on by its agents, or the form in which the tension between “academic music” and “popular music” tends to be resolved; all of these aspects are examined here.